Interventions of Corporate Social Responsibility of Oil Companies in Promoting Sustainable Community Development in Host Communities in Niger Delta, Nigeria - Ugwu, A. N.; Aruma, E. O. (Archives of Business Research, 2021)
The paper focused on intervention of corporate social responsibility of oil companies in the promotion of sustainable community development in host communities. The paper identified the strategies of corporate social responsibility intervention in the promotion of sustainable community development to include understanding the operations of corporate organizations, understanding social settings in host communities, identification of relevant stakeholders among others. The highlights of the paper on the reasons of corporate social responsibility for sustainable community development in host communities include improving people’s living conditions, satisfying the interest of many stakeholders, value-added to the operations of corporate organizations, partnership funding, an opportunity to give back to host communities, social justice among others. The paper recommends among other things that corporate social responsibility should stimulate mutual trust among relevant stakeholders as well as that corporate social responsibility should be very helpful to all the relevant stakeholders in the corporate organizations and host communities. The involvement of corporate social responsibility intervention in sustainable community development demands institutionalization of corporate organizations in development initiatives of the host communities in the society.